The Significance of Traditional Urban Public Spaces in Sustaining Place Identity in the Urban Landscape of Kerala. (2nd January 2022) - Ashfina, T.; Garg, Pushplata; Chani, P. S.
ABSTRACT: Many studies have found that a loss of place identity in urban landscapes causes a slew of social, cultural, and psychological problems. The significance of traditional urban public spaces in sustaining place identity in a cultural landscape is discussed in this paper, which employs a statistical model tailored to Kerala, specifically Calicut, and is applicable via questionnaire research. The study begins with a look at the historical context and current trends in Calicut, the state's first port town and second-most populous city. The primary goal of this study is to clarify the relationship between people and their physical environment while considering the concept of place-identity and how urban public spaces, with their unique characteristics and features, contribute to physical setting cognitions and shape place identity with a focus on Calicut. The results were obtained through field surveys. The survey had 424 participants selected using a random sampling strategy. Users are observed to have a diverse set of social and cultural traits. This study, however, only considers users who have a consistent engagement with the location including shop owners, residents, etc. The theory of urban spatial designs that play an important role in enhancing identity, specifically the factors influencing place-identity in traditional urban public spaces based on Place Identity social cohesion, and, Place Dependence will be examined in this study.